ANALISIS KUALITATIF PENGALAMAN DAN PERSEPSI PEMBELAJAR TERHADAP AKTIVITAS DIGITAL DALAM PEMBELAJARAN BAHASA INDONESIA DI MTS PANCASILA KOTA BENGKULU - Mutiara, Feni; Andra, Vebbi; Friantary, Heny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the integration of digital activities into Indonesian language learning and how this transforms traditional teaching practices by increasing student engagement and interactivity. This study focuses on the experiences and perceptions of students at MTS Pancasila in the city of Bengkulu regarding the use of digital tools in Indonesian language learning. Using a qualitative research design, this study explores students’ evaluations of digital resources, the benefits they perceive, and the challenges they face. Findings indicate that students generally use digital tools such as educational videos, online reading platforms, and social media to improve vocabulary, listening skills, and interactive language practice. Digital activities, particularly those incorporating gamification, are considered engaging and motivating. However, several challenges were identified, including insufficient structured guidance, limited feedback, and technical issues such as unstable internet connections. The research results also indicate that digital tools are more effective in supporting receptive skills, particularly listening and reading, while their contribution to productive skills such as speaking and writing remains limited without adequate instructor support. This study contributes to the field of digital learning by highlighting its strengths and limitations. This study emphasizes the.